2009
DOI: 10.1089/scd.2008.0096
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Interaction Between Cord Blood–Derived Human Neural Stem Cells and Organotypic Rat Hippocampal Culture

Abstract: The umbilical cord blood-derived neural stem/progenitor cells (HUCB-NSCs) potentially represent a rich source of transplantable material for treatment of a wide range of neurological diseases. Although, recently reported effects of their implementation in animal models of brain pathology are still controversial. As a simplified alternative to in vivo transplantation in this work we have applied a long-term organotypic rat hippocampal slice culture (OHC) as a recipient tissue to study bilateral graft/host cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…The finding does not appear to result from differences in the medium composition, as hNPCs growing on the insert membrane continued to express both markers. Interestingly, a similar suppression of GFAP expression was reported for human cord blood stem cells [12], whereas studies using mouse stem cells observed astrocytic differentiation in hippocampal cultures [9,10] and in striatal cultures [46], hinting at speciesspecific responses to the environment. The cause of this change and the extent to which the cells differ as a result, particularly in their signaling properties, require further investigation.…”
Section: Hippocampal Environment Alters the Identity Of The Progenitosupporting
confidence: 59%
See 1 more Smart Citation
“…The finding does not appear to result from differences in the medium composition, as hNPCs growing on the insert membrane continued to express both markers. Interestingly, a similar suppression of GFAP expression was reported for human cord blood stem cells [12], whereas studies using mouse stem cells observed astrocytic differentiation in hippocampal cultures [9,10] and in striatal cultures [46], hinting at speciesspecific responses to the environment. The cause of this change and the extent to which the cells differ as a result, particularly in their signaling properties, require further investigation.…”
Section: Hippocampal Environment Alters the Identity Of The Progenitosupporting
confidence: 59%
“…It has previously been demonstrated that when seeded onto organotypic hippocampal slice cultures, mouse embryonic stem cells can differentiate into functional neurons that receive synaptic input [8] and into glia [9,10]. Expression of neuronal markers has also been induced in mouse bone marrow stromal cells [11] and human cord blood-derived stem cells [12]; however, neural progenitor cells (NPCs) derived from adult rats predominantly differentiated into astrocytes when cocultured with hippocampal slices [13]. It is clear that the responsiveness to environmental cues varies between cell types, and as yet it is not clear how such environmental conditions might influence human cells.…”
Section: Introductionmentioning
confidence: 99%
“…From 4 to 7 days in vitro (DIV), serum-based culture medium was gradually changed to a serum-free medium consisting of 50% MEM-Hank’s, 25% HBSS, 25% Neurobasal-A medium, 17 mM HEPES, 2 mM l -Glutamine, 2% B-27, 5 mg/ml d -glucose, and 1% antibiotic/antimycotic (all obtained from GIBCO Life Technologies). From 7 DIV until the end of the experiment, OHCs were grown in a serum-free medium ( 64 , 66 , 67 ) to decrease astrocyte proliferation and microglial activation ( 68 , 69 ). All PI uptake and LDH release measurements, described below in more detail, were also performed in the serum-free medium due to the interference of serum with these cell viability assays ( 70 , 71 ).…”
Section: Methodsmentioning
confidence: 99%
“…Transplantation of restricted neuronal progenitors is recognized by a number of authorities in the fields of neuroscience and regenerative medicine (Goldman, ; Hofstetter et al ., ; Lindvall et al ., ; Park et al ., ). This has been further confirmed by preclinical studies in which human neuroblasts generated from cord stem cells were transplanted into organotypic rat hyppocampal culture models (Sarnowska et al ., , ; Jurga et al ., ). The first human neuro‐implantation trial for stroke was reported in 2000 (Kondziolka et al ., ).…”
Section: Methodsmentioning
confidence: 99%